2020
DOI: 10.5603/imh.2020.0013
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of citations of maritime epidemiological injury studies

Abstract: Background: The article is based on a review and follow-up of the citations of 13 epidemiological studies that aimed to improve maritime health and safety. While it's well-recognised that epidemiology is needed in occupational health and safety, the main research question: "How can epidemiology help workers to return healthy from the sea" was unanswered. Materials and methods: The 13 articles were selected as a representative sample of different epidemiological design studies intended to contribute to improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…These outcomes align with a 2005 study by Jensen et al [14], encompassing 6,461 participants, which reported an injury rate of 9.1%. Their research indicated that blows and wounds constituted 49% of injuries, followed by fractures at 12.4%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These outcomes align with a 2005 study by Jensen et al [14], encompassing 6,461 participants, which reported an injury rate of 9.1%. Their research indicated that blows and wounds constituted 49% of injuries, followed by fractures at 12.4%.…”
Section: Discussionsupporting
confidence: 89%
“…Prior studies have endeavoured to explore the reasons behind repatriation across different nationalities, with a predominant focus on accidents and trauma occurring on board ships. Additionally, investigations have been conducted on the causes of mortality among seafarers [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%